The effect of dietary protein on protein metabolism and performance in endurance-trained males - Williamson, E.; Kato, H.; Volterman, K. A.; Suzuki, K.; Moore, D. R. (Medicine & Science in Sports & Exercise, 2019)
Recommendations for dietary protein are primarily based on intakes that maintain nitrogen (i.e., protein) balance rather than optimize metabolism and/or performance.